Conflict in Management of Passive State Administrative Decision in State Administrative Dispute - Wereh, Agustien Cherly; Istislam, Dr (Faculty of Law, Universitas Brawijaya, 2018)
The government's task to achieve the state's objective is provided in the preamble of the 1945 Constitution of the Republic of Indonesia. In the governance system, societies often encounter tough situation, while administrative law has specially actualised constitutional norms of correlation between the state and its societies. The administrative management in the Law is seen as essential instrument of a democratic state of law, in which decision and/or act is determined by an entity and/or a government official or government apparatus involving executive, judicative, and legislative entities that run governmental functions which are possible to be examined at court. The research problem presented in this research is why there are differences between positive-passive system (stelsel) and negative-passive system regarding the management of state administrative decision. This research employed normative legal research along with prescriptive analysis method. The research result indicates that the emergence of conflict in passive administrative state management is caused by the inaccuracy of legislation in formulating laws.